2001
DOI: 10.1136/bmj.323.7308.310
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of variation in birth weight within normal range and within sibships on IQ at age 7 years: cohort study

Abstract: Objective To examine the relation between birth weight and measured intelligence at age 7 years in children within the normal range of birth weight and in siblings. Design Cohort study of siblings of the same sex. Setting 12 cities in the United States. Subjects 3484 children of 1683 mothers in a birth cohort study during the years 1959 through 1966. The sample was restricted to children born at >37 weeks gestation and with birth weights of 1500-3999 g. Main outcome measure Full scale IQ at age 7 years. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
230
5
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(268 citation statements)
references
References 12 publications
27
230
5
3
Order By: Relevance
“…Indeed in other within family studies the lack of any effect within siblings, when an effect is seen between families, is generally interpreted as demonstrating confounding by socioeconomic position. [17][18][19] However, the fact that adjustment for father's occupational social class had no effect on the association between education and BMI in the whole cohort suggests that this may not be the most important family-based characteristic that explains this association. Other factors, such as parental education and intelligence, neighbourhood-and schoolbased characteristics that are similar for siblings are also likely to be important.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed in other within family studies the lack of any effect within siblings, when an effect is seen between families, is generally interpreted as demonstrating confounding by socioeconomic position. [17][18][19] However, the fact that adjustment for father's occupational social class had no effect on the association between education and BMI in the whole cohort suggests that this may not be the most important family-based characteristic that explains this association. Other factors, such as parental education and intelligence, neighbourhood-and schoolbased characteristics that are similar for siblings are also likely to be important.…”
Section: Discussionmentioning
confidence: 94%
“…Such sibling studies are increasingly used in life course epidemiology. They have been used to examine the extent of confounding by parental and family factors in the associations of birth weight with childhood intelligence [17][18][19][20] and of birth weight with adult blood pressure. 21 However, we are unaware of any such sibling study in the assessment of the association between childhood intelligence/educational attainment and adult BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies correlating cord blood DHA status at birth and visual and intellectual function either suggest that there is no link (Bakker et al, 1999;Ghys et al, 2002) or they imply a negative association; it has been reported that DHA status is inversely proportional to birth weight (Rump et al, 2001), yet there is a wellestablished positive relationship between birth weight and IQ in the general population (Matte et al, 2001;Richards et al, 2001). However, such observational studies have to be interpreted with caution as cord blood levels are actually the net result of placental supply and fetal utilisation and may not correlate exactly with fetal availability.…”
Section: Implications For Dietary Recommendationsmentioning
confidence: 99%
“…As detailed above, heavier birth weights are associated with increased intelligence [2]. While the current study cannot comment on whether or not the seasonal changes in size and shape persist into adult, other studies have reported an association between season of birth and adult height [19,51].…”
Section: Implications For Population Healthmentioning
confidence: 74%
“…In addition to providing insights into prenatal development, this variable is known to be associated with a wide range of important cognitive, behavioural and health outcomes in infancy, childhood and adulthood. For example, even within the normal range of birth weights, heavier birth weight has been associated with superior neurocognitive outcomes in several cohort studies [2][3][4][5][6]. There is accumulating evidence linking birth weight and wide range of chronic, adult-onset disorders [7,8].…”
Section: Introductionmentioning
confidence: 99%